The Conjuring Girdles of King Solomon and Doctor Faustus in Early Modern Material Magic - Skemer, Don C. (Aries, 2026)
The article concerns conjuring girdles in early modern material magic, particularly in Central Europe during the long eighteenth century (c. 1660-c. 1820). Magicians in ritual circles could wear such girdles on the body as belts or sashes to conjure and command angels, spirits, and demons. Emphasis in the article is on anonymous German manuscript books of learned magic dating from the late seventeenth and early eighteenth century, with pseudepigraphal attributions to King Solomon and Doctor Faustus. These manuscripts explain the design, text, imagery, materials, measurements, production, and applications of conjuring girdles. The article also discusses what is known about their compilers, end-users, and readers during a period marked by hybridizing, variability, and democratization in material magic. The article includes three illustrations in books of learned magic with designs for conjuring girdles (Göttingen, Niedersächsische Staats- und Universitätsbibliothek, Cod. Ms. Hist. Nat. 80; Leipzig, Universitätsbibliothek, Cod. Mag. 6 [no. 51]; Leipzig, Universitätsbibliothek, Cod. Mag. 133 [no. 27]); and two conjuring scenes from the legends of Doctor Faustus and his apprentice Christoph Wagner.